Roots of Financial Literacy - Antonia Grohmann; Roy Kouwenberg; Lukas Menkhoff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Our study aims to uncover the roots of financial literacy. Better financial literacy predicts more informed savings and borrowing decisions in our sample, covering the urban middle-class in an emerging economy. We then test education at school, family background, parental teaching, and childhood experiences with money as potential determinants of financial literacy. In addition to risk tolerance and having basic numeracy skills, we find that family variables matter most, in particular better education of the mother and encouragement to save by parents. Our findings suggest that regular formal education may play only a limited role in shaping financial literacy
Keywords: D14; D20; O16; 330